Systemic Risk, Contagion, and State-Dependent Sensitivities in Value-at-Risk Estimation: Evidence from Hedge Funds - Reint E. Gropp; Zeno Adams; Roland Füss (Verein für Socialpolitik, 2010)
In this paper, we propose a state-dependent VaR (SDVaR) to estimate spill over effects among different financial institutions. We permit spill-over effects to change depending on the state of financial markets. We show that spill-over effects only exist during crisis periods; in calm times spill over effects tend to be zero. The results highlight that spill over probabilities that do not condition on the state of financial markets may substantially over- or understate the contribution of an asset class to systemic risk. Using this approach we show that hedge funds play a major role in the transmission of shocks to the other financial institutions.
Keywords: G23; C33; G14; 330; State-dependent sensitivity (SDS) value-at-risk; systemic risk; contagion; quantile regression; hedge funds